BBX21 Integrates Brassinosteroid Biosynthesis and Signaling in the Inhibition of Hypocotyl Growth under Shade - Gómez-Ocampo, Gabriel; Crocco, Carlos D; Cascales, Jimena; Oklestkova, Jana; Tarkowská, Danuše; Strnad, Miroslav; Mora-Garcia, Santiago; Pruneda-Paz, José L; Blazquez, Miguel A; Botto, Javier F (Plant & cell physiology, 2024)
B-Box-containing zinc finger transcription factors (BBX) are involved in light-mediated growth, affecting processes such as hypocotyl elongation in Arabidopsis thaliana. However, the molecular and hormonal framework that regulates plant growth through BBX proteins is incomplete. Here, we demonstrate that BBX21 inhibits the hypocotyl elongation through the brassinosteroid (BR) pathway. BBX21 reduces the sensitivity to 24-epiBL, a synthetic active BR, principally at very low concentrations in simulated shade. The biosynthesis profile of BRs showed that two active BR-brassinolide and 28-homobrassinolide-and 8 of 11 intermediates can be repressed by BBX21 under white light (WL) or simulated shade. Furthermore, BBX21 represses the expression of CYTOCHROME P450 90B1 (DWF4/CYP90B1), BRASSINOSTEROID-6-OXIDASE 1 (BR6OX1, CYP85A1) and BR6OX2 (CYP85A2) genes involved in the BR biosynthesis in WL while specifically promoting DWF4 and PHYB ACTIVATION TAGGED SUPPRESSOR 1 (CYP2B1/BAS1) expression in WL supplemented with far-red (WL + FR), a treatment that simulates shade. In addition, BBX21 represses BR signaling genes, such as PACLOBUTRAZOL RESISTANCE1 (PRE1), PRE3 and ARABIDOPSIS MYB-LIKE 2 (MYBL2), and auxin-related and expansin genes, such as INDOLE-3-ACETIC ACID INDUCIBLE 1 (IAA1), IAA4 and EXPANSIN 11 in short-term shade. By a genetic approach, we found that BBX21 acts genetically upstream of BRASSINAZOLE-RESISTANT 1 (BZR1) for the promotion of DWF4 and BAS1 gene expression in shade. We propose that BBX21 integrates the BR homeostasis and shade-light signaling, allowing the fine-tuning of hypocotyl elongation in Arabidopsis.
Keywords: Signal Transduction; Arabidopsis; světlo; regulace genové exprese u rostlin; brassinosteroidy; Gene Expression Regulation, Plant; Brassinosteroids; regulátory růstu rostlin; Shade light; Hypocotyl; Light; BBX21; Brassinosteroids (BRs); hypokotyl; Cytochrome P-450 Enzyme System; Arabidopsis Proteins; transkripční faktory; Plant Growth Regulators; proteiny huseníčku; systém (enzymů) cytochromů P-450; Transcription Factors; signální transdukce; BZR1